The waiting game: Anticipatory stress and its proliferation during jail incarceration - Turney, Kristin (Criminology, 2024)
Anticipatory stress—or worries about the future that produce emotional distress—may explain some of the deleterious repercussions of incarceration for health. We use nearly 500 interviews with incarcerated men and their family members to describe anticipatory stress stemming from the stressor of jail incarceration, a commonly experienced but understudied type of confinement distinct from prison incarceration. We identify and explain how jail incarceration involves a powerful confluence of factors that give rise to anticipatory stress about adjudication, family relationships, the well-being of loved ones, and reintegration. We describe three types of anticipatory stress proliferation between incarcerated men and their families. First, anticipatory stress commonly proliferates from incarcerated men to their children's mothers and their own mothers, with anticipatory stress being particularly salient when it involves the possibility of major changes, system irrationality, and powerlessness. Second, family members can experience anticipatory stress regardless of whether their incarcerated loved one reports anticipatory stress, shaped in part by men's extensive criminal legal contact. Third, family members with weak relationships with incarcerated men generally do not experience anticipatory stress despite the anticipatory stress endured by their incarcerated loved ones. This study provides a framework for understanding how other stages of criminal legal contact contribute to health inequalities among incarcerated people and their families.